’THE INFLUENCE OF COMMUNITY JOB TRAINING AND COMPENTENCY TOWARD LABOR ABSORPTION IN SUKABUMI REGENCY - YULIANTHI SUMINAR; SAKTI ALAMSYAH; ASEP HIKMAT (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This study focuses on the effect of community job training and competence on labor absorption in Sukabumi Regency on job training participants at UPTD Job Training Center (BLK) Sukabumi Regency. The research used is quantitative research with an associative approach. The sample of this research is the alumni of the Sukabumi Regency Job Training Center who are absorbed in the Sukabumi Regency area. Samples were carried out by saturated sampling method. Data was collected by using a questionnaire using a rating scal model. which were distributed to alumni of the Job Training Center as many as 60 questionnaires. While the data analysis technique used is the product moment correlation analysis technique using the SPSS v.25.0 application and the Linear Regression analysis technique, by testing the hypothesis test statistic test t test. The results of the study show that there is a significant correlation between community job training and employment, there is also a significant correlation between competence and employment, community job training and competence simultaneously affect employment, community job training has a significant positive effect on employment workforce, competence has a significant positive effect on job absorption, community job training and competence simultaneously have a significant effect on employment.